Village Transformation through SDGs Concept: Tackling Digital Crime, Stunting, Improving Religiousness through Education and Waste Management: Community Service - Syafana, Firziawan Adam; Purnomo, Halim; Fauzi, Aulia Andhara; Dzakwan, Abdillah; Zenn, Darell; Mawaddah, Dien; Satria, Enggi Fajar Dimas; Al Farizi, Iqbal Luthfiansyah; Nugroho, Muhammad Fakhri; Amir, Naufal Fikri; Asya, Putri Asti Noor; Annisa, Yolanda Ayu; Rahmatika, Dien Noviany (Universitas Pancasakti Tegal, 2024)
This article discusses village transformation through the implementation of the Sustainable Development Goals (SDGs) concept with a focus on tackling digital crime, stunting, and increasing religiosity. In this context, the village integrates digital approaches in education and waste management as part of sustainable development efforts. Tackling digital crime is done through community socialization and education on cyber threats, while health and nutrition programs are implemented to address stunting. In addition, increased religiosity is achieved through education at the Qur'anic Education Park (TPA) by utilizing technology to strengthen religious values. Effective waste management is also part of the initiative to maintain environmental health and quality of life. This article examines the impact of this transformation on the village community and how the synergy between technology, health, education and religiosity can support the overall achievement of the SDGs.